ANALISA INFAQ SEBAGAI RULE MODEL TRANSAKSI PEMBAYARAN PADA PENERAPAN SISTEM PERDAGANGAN EKONOMI BERBASIS SYARIAH. - Arya Rizki Wardana (Jurnal Al Wadiah, 2023)
Infaq is one of the pillars of Islamic economics that plays an important role in income distribution and social welfare. Infaq can be implemented as a rule model for payment transactions in the implementation of a sharia-based economic trading system. This study aims to analyze infaq as a rule model for payment transactions in the implementation of a sharia-based economic trading system. The research method used is a qualitative method with a descriptive approach. Data were obtained through literature studies and interviews with experts in the field of Islamic economics. The results of the study show that infaq can be implemented as a rule model for payment transactions in the implementation of a sharia-based economic trading system. Infaq can be applied as a condition or obligation for transaction actors to set aside a portion of their income for social purposes. Infaq can be implemented through a digital payment system that is integrated with infaq management institutions.